Extreme horseshoe and circumanal anal fistulas-challenges in diagnosis and management - Pankaj Garg; Baljit Kaur; Vipul D Yagnik; Geetha R Menon (Tzu Chi Medical Journal)
Objectives: Extreme horseshoe anal fistulas are rare, and there are little data on the diagnosis and management of these fistulas. Materials and Methods: Patients with horseshoe anal fistula, in which the fistula tract encircled more than 75% of the anal circumference were included in the study. All patients were assessed by a preoperative magnetic resonance imaging (MRI). The patients were managed by a sphincter-sparing procedure. The continence was evaluated by an objective continence scoring system (Vaizey's scores). Results: 1059 anal fistula patients were operated on over 7-years with a median follow-up of 36 months (range: 5–79 months). There were 47/1059 (4.4%) patients with extreme horseshoe anal fistulas. In 4/47 patients, the fistulas were complete circumanal (encircling anal canal completely). The mean age was 39.5 ± 10.9 years, M/F-41/6. The fistula was supralevator in 12/47 (25.5%), had an associated abscess in 28/47 (59.6%), and was recurrent in 33/47 (70.2%) patients. The tracts were intersphincteric in 27/47, transsphincteric in 2/47, and both (intersphincteric and transsphincteric) in 18/47 patients. All patients (n = 47) were managed by a sphincter-sparing procedure. Four patients were lost to follow-up. The fistula healed completely in 34/43 (79%) patients. There was no significant difference between preoperative and postoperative Vaizey's continence scores 0.031 ± 0.17 and 0.033 ± 0.18 respectively (P=0.90, Mann–Whitney U-test). Conclusion: Extreme horseshoe fistulas are rare, with an incidence of about 4% (in a referral practice). The missed diagnosis of circumferential tracts could lead to a recurrence. MRI was pivotal to confirm the diagnosis. Proper identification and management of internal opening and adequate drainage of all tracts were crucial for successfully treating extreme horseshoe fistulas.